Diagnosis Confirmation of Inclusion Bodies Hepatitis on Broiler Chicken using Polymerase Chain Reaction Method - Rahmahani, Jola; Kirana, Maha; Rantam, Fedik Abdul; Suwarno, Suwarno (Universitas Airlangga, 2022)
This study aimed to diagnose cases of Inclusion Bodies Hepatitis (IBH) in broiler chickens. A total of 6 chickens were collected from farms in Banten and Jember. Samples were taken from the liver which underwent changes such as brittle, yellowish in color and enlarged. The samples were ground and extracted, then the Polymerase Chain Reaction (PCR) test was performed using Primers Hexon A (5'-CAARTTCAGRCAGACGGT-3') and Hexon B ( 5'-TAGTGATGMCGSGACATCAT-3' ) with 897 bp length. The results showed that the broiler chicken case sample from Banten was positively 100% infected by the IBH Virus.